Effect of Exercise on Fatty Acid Metabolism and Adipokine Secretion in Adipose Tissue - Mika, Adriana; Macaluso, Filippo; Barone, Rosario; Di Felice, Valentina; Sledzinski, Tomasz (Frontiers in Physiology, 2019)
Increased physical activity is an optimal way to maintain a good health. During exercise, triacylglycerols, an energy reservoir in adipose tissue, are hydrolyzed to free fatty acids which are then released to the circulation, providing a fuel for working muscles. Thus, regular physical activity leads to a reduction of adipose tissue mass and improves metabolism. However, the reduction of lipid reservoir is also associated with many other interesting changes in adipose tissue fatty acid metabolism. For example, a prolonged exercise contributes to a decrease in lipoprotein lipase activity and resultant reduction of fatty acid uptake. This results in the improvement of mitochondrial function and upregulation of enzymes involved in the metabolism of polyunsaturated fatty acids. The exercise-induced changes in adipocyte metabolism are associated with modifications of fatty acid composition. The modifications are adipose tissue depot-specific and follow different patterns in visceral and subcutaneous adipose tissue. Moreover, exercise affects adipokine release from adipose tissue, and thus, may mitigate inflammation and improve insulin sensitivity. Another consequence of exercise is the recently described phenomenon of adipose tissue “beiging”, i.e. a switch from energy-storing white adipocyte phenotype to thermogenic fatty acid oxidizing beige adipocytes. This process is regulated by myokines released during the exercise. In this review, we summarize published evidence for the exercise-related changes in fatty acid metabolism and adipokine release in adipose tissue, and their potential contribution to beneficial cardiovascular and metabolic effects of physical activity.